Building a relationship between international doctoral students and their thesis supervisors through an online community of practice: Findings from a Systematic Literature Review - Crosta, Lucilla; Gray, Morag (Proceedings of the International Conference on Networked Learning, 2014)
This paper presents an extract from a systematic international literature review research work funded by Laureate Online Education and aimed at detecting best practice in online doctoral students’ supervision. It was carried between March and July 2013 out by the authors of the paper, who have been working as online tutor and thesis supervisors at the University of Liverpool in the Online Professional Doctorate of Education (EdD). Prof. Morag Gray is also the Thesis Supervisor Manager in the EdD and she has been working recently for the implementation of the Thesis stage of this same programme. The authors initially illustrated the meaning of supervision as mentoring since while doctoral advising is related to accomplishing doctoral requirements, mentoring refers to both career and psychosocial support to students (Lunsford, 2012). The paper focuses on the idea that student-supervisor relationship is pivotal in student’s success and progress in research and on the idea that the use of a community of practice among supervisors and students may help in sustaining doctoral distance students on their journey and to overcome their sense of loneliness while working online. Some information on the way how the systematic literature review has been carried out is given in the paper namely: the research main aims and objectives, the literature search strategy, the search term used in the work and so on. This work makes an attempt to create connections with the online environment and on how it might be possible to sustain and to enhance the supervisor-student relationship via the internet when doctoral students and supervisors coming from different parts of the world, and who have never met in person. Particularly Andrew (2012) proposed the use of an online community of practice and of regular e-meetings for supporting online students’ work and relationship, also among doctoral students themselves, whilst Rosset & Marino (2005) shared experience on e-coaching providing some interesting insights on the possible use of technology for distance communication purposes and related effects on the individual’s relationship. Hence this paper provides some linkages between the Networked Learning practice and the use of the community of practice metaphor for connecting doctoral students and supervisors